Exoskeletons vs. exosuits: A comparative analysis using biological-based computer simulation - Bermejo-García, Javier; Romero-Sánchez, Francisco; Agujetas, Rafael; Sánchez, Francisco Javier Alonso (Computers in biology and medicine, 2024)
Interest in the design of gait assistance devices has experienced significant growth in recent years. Among various uses of assistive devices, those aimed at supporting the elderly have gained importance due to the rising population of this age group. This study aims to compare the efficacy of two types of assistive devices through musculoskeletal simulations. One case is an ideal device, simulating the motor actuation as it would be in a rigid exoskeleton, and, cable-assisted devices, simulating the assistance of an exosuit. The simulations were based on data obtained from 9 subjects. OpenSim, an open-source software, was employed to conduct the simulations. Our findings indicate that the cable-assisted device outperforms the traditional exoskeleton by achieving a more significant reduction in the metabolic cost with relatively lower assistance power. Cable-assisted gait assistance devices have shown comparable results to traditional exoskeletons, with the added advantage of improved performance through reduced power requirements. •Assisted human gait with various assistance types was simulated in OpenSim.•Both types of assistance reduce the metabolic costs of the muscles.•Cable actuation more effectively reduces metabolic cost than an ideal device.•Hip gait assistance in the elderly helps reduce individual muscle torque.